Recent developments and future prospects in the treatment of visceral leishmaniasis. (June 2016) - Sundar, Shyam; Singh, Anup
Limited therapeutic options in visceral leishmaniasis (VL) make the treatment of this neglected disease very challenging. In addition to this, long treatment duration and toxic adverse effects make it even more difficult. With no effective vaccine available to date, treatment of VL is based only on chemotherapy. In the Indian subcontinent, a single dose of liposomal amphotericin B (L-AmB) and multidrug therapy (L-AmB + miltefosine, L-AmB + paromomycin [PM], or miltefosine + PM) are the treatments of choice for VL. In East Africa, however, combination therapy of pentavalent antimonials (Sb v ) and PM remains the treatment of choice, and in the Mediterranean region and South America, L-AmB is the recommended drug. Fexinidazole and PA-824 are new promising drugs which have shown encouraging results in preclinical studies.